Selection of local prebiotics to support the growth of probiotic bacteria and fish - Dian Eka Ramadhani; Cecilia Eny Indriastuti; M Agung Zaim Adzkiya; Muhammad Arif Mulya; Andri Iskandar; Nida Ulzanah (Universitas Djuanda, 2025)
Fish production in Indonesia is increasing, but the main obstacle that can hinder the continuity of the cultivation process is disease attacks. Antibiotics are ingredients commonly used to treat fish diseases. However, antibiotics can have negative effects, so other alternatives are needed to overcome this problem. The use of prebiotics in Indonesia still comes from abroad, whereas Indonesia has many ingredients that can be developed into prebiotics. This research aims to identify and select local prebiotic sources that have the potential to meet scientific criteria as probiotics. The research method was carried out in vitro to determine the glucose, maltose, and fructose content in purple sweet potato, banana stem, cream sweet potato, yam tuber and yellow sweet potato. The highest maltose content is produced by purple sweet potatoes (2.61%), fructose content is produced by yellow sweet potatoes (1.80%), and glucose content is produced by creamy sweet potatoes (2.15%). The results of this study need to be further developed into probiotics that can be used to support sustainable aquaculture.